COMPARATIVE STUDY ON THEORETICAL MODELS AND DESIGN CODES FOR THE SHEAR CONTRIBUTION OF NSM FRP BARS IN RC BEAMS (Jurnal Teknologi (Sciences & Engineering), 2016)
This paper presents a comparative study on various theoretical models and design codes for the shear contribution of Near-Surface Mounted (NSM) using Fibre Reinforced Polymer bars to reinforced concrete (RC) beams. Theoretical models from De Lorenzis and A. Nanni, Anwarul Islam and Diaz and Barros, and ACI440.1R-06 and CSA-S806 design codes were selected. All the equations were compared by integrating experimental parameters from Rizzo and De Lorenzis, and Cisneros D. et al. From analysis, it was observed that the theoretical models shows substantial differences by underestimating the experimental findings of Rizzo and De Lorenzis from -68% to -38%. Similarly with Cisneros experimental work, the three theoretical models also produces large differences ranging from -73% to +41%. The analysis from the two design codes from ACI440.1R-06 and CSA-S806 also resulted with both design codes having significant differences ranging from -60% to +48%. However, from close observation, Dias and Barros theoretical model showed more accuracy by having a difference of just -4% with ACI440.1R-06 design code giving a much higher but acceptable difference of +26% compared to CSA-S806 at -60%.Â